The Use of Song in Improving Students’ Listening Skill - Ni Luh Eka Yuliarini (Indonesian Journal Of Educational Research and Review, 2022)
Listening skill is one of the skills that should be mastered. However, many students have difficulty at the listening sessions, especially in understanding what the speaker is saying. It is because they have lack of background knowledge to support their listening. To improve their listening skill, a suitable strategy is needed. The use of songs in the listening classroom can increase students’ interest. Therefore, this study aimed at finding information on the use of song in improving students’ listening skill. This study and used library research. The finding of this study was gathered after reading and analyzing articles in online media. This article provides some findings such as the information about how to implement songs, and the other findings are the students’ listening scores improved after implementing song and students can expand their vocabularies. Using song as a medium can be a good strategy to motivate students to practice their listening.